Using Multiple Regression Analyses to Uncover Patterns of Correlates of Grief Problems, Depression and Suicidal Ideation Among Suicide Bereaved Individuals. (June 2023) - Feigelman, William; Cerel, Julie; Sheehan, Lindsay; Oexle, Nathalie
This analysis of a convenience sample survey of 195 suicide bereaved adults focuses on predictors of three important highly interrelated experiences among the suicide bereaved: grief problems, depression and suicidal thinking. Although each of these three experiences can be explained by a unique set of predictors, they share many commonalities. Several predictors stood out especially in either aggravating or alleviating these experiences: personal (or post-traumatic) growth, perceived social support, feelings of blameworthiness, perceived suicide stigma, years since loss and a respondent's mental health difficulties experienced prior to their suicide loss. We also review the clinical implications of these results.